Unstable approach in aviation : causal factors and preventive interventions - Lee, Basil Wei Jie (2017)
This research investigates on the reasons behind the occurrence of unstable approach during the approach and landing phase of flight. Pilots in the cockpit environment are not the only operators responsible for the safety of the aircraft. Air Traffic Control Officers also play a part in ensuring that instructions communicated through the radio frequencies are accurate and succinct. A total of 8 pilots were interviewed for a study on the occurrence of unstable approach during the approach and landing phases of flight. The interview lasted for an hour each and pilots were asked to recall a scenario which could harm the ultimate landing stability of the aircraft. Questions related to the interactions between the Air Traffic Control Officers and pilots were asked and how the pilots eventually executed the instructions. Most cases highlighted occurred during peak hours when Air Traffic Control Officers were busier and there were more aircrafts under control. Pilots with more flight experience could better predict the subsequent states of the aircraft and help Air Traffic Control Officers with air traffic separation by looking at various cues such as crosschecking communication between other parties in the radio frequency and their on-board instruments. Individual goals of Air Traffic Control Officers and pilots were different and their Shared Mental Model was discussed. Pilots would prefer if Air Traffic Control Officers have better Shared Mental Model whilst giving instructions by understanding the aircraft’s performance better. The cooperation, communication and coordination between both parties would also affect their shared goals and the research highlights the steps taken by pilots currently and how it can be improved. After highlighting the contributing factors from the perspective of the pilots, more research can be carried out from the Air Traffic Control Officers’ perspective into how both operators can complement each other while achieving their shared goals without compromising on their individual goals.